Dementia patient care in the diagnostic medical imaging department. (October 2018) - Challen, R.; Low, L.-F.; McEntee, M.F.
Abstract: Introduction: People with dementia have difficulties with memory, executive functions and behaviour which pose a challenge during diagnostic imaging. There is abundant literature on the radiographic diagnosis of dementia; however, there is little research on how to best to care for people with dementia during imaging procedures. The aim of this study is to explore the experiences of dementia care in imaging departments through the perspectives of people with dementia, carers, radiographers and student radiographers. Methods: This was a cross-sectional qualitative study. Four people with dementia and six carers participated in individual semi-structured interviews; eight academic radiographers and 19 student radiographers participated in focus groups. Interviews and focus groups were transcribed and thematically analysed. Results: Participants described positive and negative experiences during imaging procedures. Common themes existed among people with dementia, carers and radiographers. Findings were (1) People with dementia and carers had negative experiences such as distress and pain; radiographers experienced stigma and violence. (2) Negative experiences during imaging were associated with disrespected personhood, poor communication, insufficient knowledge of dementia, inappropriate time management, overly stimulating physical environments and exclusion of carers. (3) Departmental protocols that contributed to negative experiences included lack of preparation, lack of dementia protocols, and the use of restraints. Conclusion: People with dementia and their carers can experience poor care in imaging departments and radiographers can find it difficult working with people with dementia. Radiographers need training about dementia, imaging services can improve their procedures and environment, and work in greater partnership with carers. Highlights: People with dementia receiving poor patient care in medical imaging departments. Personhood must be respected for positive and successful imaging procedure. Communication, preparation, education, time management vital to positive experience. People with dementia, carers, radiographers disagree with current practices. Radiographers grossly underprepared for image people with dementia.